The Association Between Recurrence of Atrial Fibrillation and Revascularization in Patients With Coronary Artery Disease After Catheter Ablation - Chen, Xiaowei; Zhao, Jiangtao; Zhu, Kui; Qin, Fen; Liu, Hengdao; Tao, Hailong (Frontiers in Cardiovascular Medicine, 2021)
Abstract Aim: The connection between revascularization for coronary artery disease (CAD) and the incidence of recurrent events of atrial fibrillation (AF) after ablation is unclear. This study aimed to explore the relationship between coronary revascularization and AF recurrence in patients who underwent radiofrequency catheter ablation (RFCA). Methods: 419 patients who underwent performed coronary angiography at the same time as RFCA were enrolled in this study. Obstructive CAD was defined as at least one coronary artery vessel stenosis of ≥75% and percutaneous coronary intervention (PCI) was recommended. Non-obstructive CAD was defined as coronary artery vessel stenosis of <75%.The endpoint was freedom from recurrence from AF after RFCA during the 24-month follow-up. Results: In total, 102, 95, and 212 patients were undergone coronary angiography and diagnosed as having obstructive CAD, Non-obstructive CAD, and Non-CAD, respectively. During the 24-month follow-up period, patients without obstructive CAD were significantly more likely to achieve freedom from AF than patients with obstructive CAD (hazard ratio [HR]: 1.72; 95% confidence interval [CI]: 1.23–2.41; P = 0.001). The recurrence rate of AF was significantly lower in patients who underwent PCI than in those who did not (HR: 0.45; 95% CI: 0.25–0.80; P = 0.007). Conclusions: This study suggests that obstructive CAD is associated with a higher rate of AF recurrence. Additionally, For patients with CAD, coronary revascularization is related to a lower recurrence rate of AF after RFCA.